CORRELATION BETWEEN MAGNESIUM SERUM LEVELS AND PEAK EXPIRATORY FLOW IN CHRONIC ASTHMA PATIENTS - Grendi Faneri Yonarko; Suhardi Darmo Atmojo; Barmawi Hisyam (Acta Interna The Journal of Internal Medicine, 2011)
ABSTRACT Background: Magnesium Serum in some previous studies had been related to asthma events and severity levels. Correlation between magnesium serum levels and severity of asthma was controversies. It might be influenced by race, genetic pattern, diet and demography factor.Objective: The objective of this study was to know relationship between magnesium serum levels and predictive PEF (Peak Expiratory Flow) in chronic asthma patients in Yogyakarta.Method: This was a cross-sectional study; subjects were asthma patients who visited Pulmonology Outpatient Department in Dr. Sardjito General Hospital Yogyakarta, from September 2004 - March 2005. We performed clinical evaluation, magnesium serum levels (normal 0.65 mmol/L-1.04 mmol/L), predictive PEF and medications. Correlation between magnesium serum levels and PEF were analyzed by Pearson correlation test. This study used analysis of variance (anova) to analyze mean difference among more than 2 groups and multiple regressions to know the variables which influenced serum magnesium levels.Result: There were 62 asthma patients in this study. There was no hypomagnesaemia. The mean of magnesium was 0.89 ± 0.08 mmol/L. Results showed that serum magnesium levels and predictive PEF had weak correlation (r= 0.281; p=0.027). There was no significant correlation between admission rate to Emergency Room due to asthma by magnesium levels (r=0.029 p= 0.8).Conclusion: Results showed weak relationship serum magnesium levels and PEF in chronic asthma patients. Keywords: bronchial asthma; serum magnesium levels, Peak Expiratory Flow rate